2022
DOI: 10.1136/bmjopen-2021-054769
|View full text |Cite
|
Sign up to set email alerts
|

Overestimating women’s representation in medicine: a survey of medical professionals’ estimates and their(un)willingness to support gender equality initiatives

Abstract: ObjectiveAmidst growing numbers of women in certain areas of medicine (eg, general practice/primary care), yet their continued under-representation in others (eg, surgical specialties), this study examines (1) whether medical professionals mistakenly infer that women are now broadly well represented, overestimating women’s true representation in several different areas and roles; and (2) whether this overestimation of women’s representation predicts decreased support for gender equality initiatives in the fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…They can also help us understanding how workplace experiences can affect gendered workplace choices (e.g. Begeny et al, 2022 ; Meeussen et al, 2022 ; Morgenroth et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They can also help us understanding how workplace experiences can affect gendered workplace choices (e.g. Begeny et al, 2022 ; Meeussen et al, 2022 ; Morgenroth et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as Feenstra et al ( 2020 ) argue, rather than being seen as a personal problem that plagues individual women, it is critical to acknowledge the role that the social and organizational context plays in eliciting feelings of impostorism (see also Kark et al, 2022 ). Indeed, a series of studies by Begeny et al ( 2022 ) demonstrate that impostor feelings can be seen as is a direct response to how one is treated by others. In a longitudinal study, we showed that that experiencing fewer expressions of distinctive treatment, such as being asked for advice, resulted in a significant increase in impostor feelings over time.…”
Section: When We Try To Fix Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with this growing number of women in medical schools, it is interesting how medical professionals may mistakenly infer that women are now broadly well-represented, overestimating the true representation. The misperception could produce growing reservations or less support for gender equality initiatives and political support ( 26 ).…”
Section: Barriers To Entering and Remaining In The Cmr Fieldmentioning
confidence: 99%
“…There’s a triple whammy of negative perceptions, difficult structures (especially around child rearing), and a lack of support to undertake leadership roles. Many doctors don’t appreciate that women in medicine have a different experience—and they therefore don’t consider change to be necessary 8. Some of us in healthcare don’t realise how our own behaviour can be misinterpreted, nor how easy it is to change 9…”
mentioning
confidence: 99%